A call for a more rigorous screening of postoperative delirium - Koch, Susanne; Radtke, Finn; Spies, Claudia (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
With the publication of the “Electroencephalography Guidance of Anesthesia to Alleviate Geriatric Syndromes (ENGAGES)” trial, Wildes and colleagues presented the results of a prospective, randomized, controlled, single-center trial aiming to analyze whether intraoperative electroencephalography (EEG) guidance could reduce the rate of postoperative delirium (POD) (1).